Integral Superposition-Type Operators on Some Analytic Function Spaces - A. El-Sayed Ahmed; S. Omran (Journal of Function Spaces)
All entire functions which transform a class of holomorphic Zygmund-type spaces into weighted analytic Bloch space using the so-called n-generalized superposition operator are characterized in this paper. Moreover, certain specific properties such as boundedness and compactness of the newly defined class of generalized integral superposition operators are discussed and established by using the concerned entire functions.